2020
DOI: 10.1124/dmd.120.090639
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in miRNA Expression Influence GSTZ1 and Other Drug Metabolizing Enzymes

Abstract: Previous work has shown that hepatic levels of human glutathione transferase zeta 1 (GSTZ1) protein, involved in tyrosine catabolism and responsible for metabolism of the investigational drug dichloroacetate, increase in cytosol after birth before reaching a plateau around age 7. However, the mechanism regulating this change of expression is still unknown, and previous studies showed that GSTZ1 mRNA levels did not correlate with GSTZ1 protein expression. In this study, we addressed the hypothesis that microRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The miRNAs overexpress or under-express affecting the expression of the gene, and likewise, the expression of the related pathways causing lesions. MiRNA is a potential biomarker for treatment response monitoring and diagnosis, and an imminent new treatment target ( Jahn et al, 2020 ). From clinical trials to laboratory tests, doctors should expect stable miRNA formulas.…”
Section: Discussionmentioning
confidence: 99%
“…The miRNAs overexpress or under-express affecting the expression of the gene, and likewise, the expression of the related pathways causing lesions. MiRNA is a potential biomarker for treatment response monitoring and diagnosis, and an imminent new treatment target ( Jahn et al, 2020 ). From clinical trials to laboratory tests, doctors should expect stable miRNA formulas.…”
Section: Discussionmentioning
confidence: 99%
“…169 In addition, Jahn et al showed that miR-376c-3p prevents the expression of GSTZ1 by repressing translation, and the expression of this miRNA is lower in adults than in children, which provides new ideas for studying the factors that influence GSTZ1. 170 GSTZ1 genotypes are also important in influencing the metabolism of DCA. 171 There are five common haplotypes based on the three common asynchronous single-nucleotide polymorphisms (rs7975, rs7972, rs1046428) in the GSTZ1 gene coding region, which, in order of population frequency, are EGT (GSTZ1C, 50%), KGT (GSTZ1B, 28%), EGM (GSTZ1D, 15%), KRT (GSTZ1A, 7%), and KGM (GSTZ1F, 0.4%).…”
Section: Barriers To the Clinical Application Of Dca And Possible Cop...mentioning
confidence: 99%
“… 169 In addition, Jahn et al showed that miR-376c-3p prevents the expression of GSTZ1 by repressing translation, and the expression of this miRNA is lower in adults than in children, which provides new ideas for studying the factors that influence GSTZ1. 170 …”
Section: Barriers To the Clinical Application Of Dca And Possible Cop...mentioning
confidence: 99%
“…The data support the role of the age-dependent miRNAs in regulating drug-metabolizing enzyme genes, including several CYP genes. Age-related changes in miRNA expression also influence ontogeny of a phase II enzyme of glutathione transferase zeta 1 (GSTZ1) in human liver (Jahn et al, 2020). miRNAs as a major epigenetic mechanism in posttranscriptional regulation of drug metabolizing enzymes has been referred as miRNA pharmacoepigenetics, which may serve as a new strategy for development of more effective therapy (Yu et al, 2016).…”
mentioning
confidence: 99%